DAMPAK PEMBEBASAN LAHAN PERTANIAN UNTUK JALAN TOL SURABAYA - MOJOKERTO (SUMO) TERHADAP KUALITAS HIDUP PETANI BEKAS PEMILIK LAHAN DI SUMBERWARU, WRINGINANOM – GRESIK - Handayani, Mei Fatul; Parsudi, Setyo; Sudarto, Teguh (Berkala Ilmiah AGRIDEVINA, 2016)
This study aims to determine the implementationof agricultural land acquisition for toll roads, to know theperception of farmers on land acquisition, and to analyze theimpact of land acquisition on the quality of life of formerlandowners. The locationof this research is in Sumberwaruvillage Kec.Wringinanom Kab.Gresik, with informants 30farmers affected by land acquisition. The data usedconsisted of primary and secondary data with quantitativedescriptive analysis. Based on the results and discussionitwas found that the land acquisition in Sumberwaru Villagewas done at the end of 2014, around October 2014. Beforethe release, the socialization, inventory, deliberation andadministration in Sumberwaru village were conducted. Theexistence of agricultural land acquisition in SumberwaruVillage Kec. Wringinanom Kab. Gresik has a positive impacton former landowners and quality of life of farmers coveringeconomic aspects, health aspects, educational aspects,social aspects, and psychological aspects.Keywords: Land Acquisition, Quality of Life